An Analysis of Grammatical Errors Made by Students in Writing Descriptive Text at The Third Year Students of English State Islamic University Imam Bonjol Padang - Dian Christina; Rasmita Rasmita (Fakultas Sastra Universitas Ekasakti, 2021)
The students usually make error on the use of grammar when they produce an English writing, also in writing descriptive text. It is due to the difference between Indonesia and English grammatical system. If the students are not able to use those aspects correctly, it would be worried that their writing which is good content and organization would not give good sense because the readers misunderstand the message conveyed. The purpose of this study was to describe types of grammar errors made by the third year students in paragraph writing. The population of this research was 68 students of the third year students of English State Islamic University Imam Bonjol Padang, which were divided into two classes: class A and B. The sample was 30 students by using cluster random sampling. This research was done by giving some topics and students had to choose one of the topics given such as “My Daily Activities”, “My Favorite Lecturer”, and “My Best Friend in this Semester”. The researcher uses qualitative method in order to obtain valid findings from 30 students of third year students of English. Based on the error analysis conducted, the researcher found that errors regarding sentence structure are the most dominant errors, with the biggest number of errors are in verb and verb groups with the biggest number of errors are in addition verb (64,10%). Then, it is followed by errors regarding nominal with the biggest number of errors are in inappropriate addition of nominal (35,90%). Last, the errors regarding pronoun with the biggest number of errors are in inappropriate selection pronoun (24,59%). The findings show that the students have difficulties in using correct sentence structure, especially in omission verb. This problem may occur due to their lack understanding of grammatical rules.